2018
DOI: 10.1113/jp274938
|View full text |Cite
|
Sign up to set email alerts
|

The myth of the immature barrier systems in the developing brain: role in perinatal brain injury

Abstract: Central nervous system homeostasis is maintained by cellular barriers that protect the brain from external environmental changes and protect the CNS from harmful molecules and pathogens in the blood. Historically, for many years these barriers were thought of as immature, with limited functions, during brain development. In this review, we will present advances in the understanding of the barrier systems during development and evidence to show that in fact the barriers serve many important neurodevelopmental f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 82 publications
(93 reference statements)
0
45
0
Order By: Relevance
“…ROS lead to nuclear translocation of the transcription factor nuclear factor-kappa B (NF-κB) subunit p65, overexpressing the pro-inflammatory cytokines IL-1β and TNF-α, leading to glial reactivity and cell death [ 25 ]. Microglia and astrocytes are the cells firstly activated by PA, as evidenced by morphological changes, migration to damaged regions, and release of: (i) pro-inflammatory cytokines, TNF-α, IL1-β, and IL-6; (ii) glutamate; (iii) nitric oxide, and (iv) additional free radicals [ 26 , 27 , 28 ], contributing to a harmful cellular environment, causing neuronal and glial death [ 29 , 30 ]. Microglial infiltration, astrogliosis and upregulation of TNF-α and IL-1β have been observed 24 h and up to 2 months after birth in white and grey matter of post-mortem brains of infants suffering from hypoxic-ischemic encephalopathy [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…ROS lead to nuclear translocation of the transcription factor nuclear factor-kappa B (NF-κB) subunit p65, overexpressing the pro-inflammatory cytokines IL-1β and TNF-α, leading to glial reactivity and cell death [ 25 ]. Microglia and astrocytes are the cells firstly activated by PA, as evidenced by morphological changes, migration to damaged regions, and release of: (i) pro-inflammatory cytokines, TNF-α, IL1-β, and IL-6; (ii) glutamate; (iii) nitric oxide, and (iv) additional free radicals [ 26 , 27 , 28 ], contributing to a harmful cellular environment, causing neuronal and glial death [ 29 , 30 ]. Microglial infiltration, astrogliosis and upregulation of TNF-α and IL-1β have been observed 24 h and up to 2 months after birth in white and grey matter of post-mortem brains of infants suffering from hypoxic-ischemic encephalopathy [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…As discussed, Saunders et al (2012) made note of the commonly held, though largely unfounded, belief that the BBB within the developing brain was "immature" and lacked full functionality. Mallard et al (2018) have devoted a review to challenging this belief even further, highlighting a variety of neurodevelopmental functions contributed to by the BBB and other barrier mechanisms in fetal and newborn brains. One recent investigation has identified that BBB function is established prior to birth, although at different developmental points for different brain areas (Ben-Zvi et al, 2014).…”
Section: Perinatal Brain Developmentmentioning
confidence: 99%
“…Despite differences in etiology (infectious versus sterile inflammation), cross-talk between the peripheral immune system and the immune-privileged brain parenchyma is central in the pathophysiology of preterm brain injury. The biochemical cascade initiated after HI and antenatal infection results in the release of danger-associated molecular patterns (DAMPs) and cytokines (IL-6 in particular) from the circulation contribute to the activation of cerebral endothelium and disruption of the blood-brain barrier, as elegantly reviewed by Mallard et al [ 85 ], thereby undermining central nervous system (CNS) immune privilege and allowing active recruitment of leukocytes that contribute to the neuroinflammatory response, which is primarily mediated by microglia [ 63 , 86 , 87 ].…”
Section: Preterm Brain Injury—timing Is Keymentioning
confidence: 99%